Electroreduction of Acetochlor at Silver Cathodes in Aqueous Media. Issue 7 (21st July 2021) - Couto Petro, Ana G.; Scherschel, Nicholas F.; Baker, Lane A.
Abstract : We report electroreduction of acetochlor at silver cathodes in aqueous media to provide insight related to electroreduction as a practical application for remediation of haloorganic pollutants. Cyclic voltammetry was used to determine the electrochemical behavior of acetochlor in water as a function of pH. Electrolysis was employed as a means for bulk reduction, with both constant-potential (CPE) and constant-current electrolysis (CCE) considered. CPE offers high selectivity and is preferred for mechanistic analysis, however, long electrolysis times are required for complete reduction. In contrast, CCE was found to provide an alternative for fast electroreduction of acetochlor, with the caveat that current densities must be chosen carefully, to retain selectivity against competing reactions (e.g., proton reduction). In addition, the effect of cell configuration (divided vs undivided) was explored. Finally, an undivided parallel-plate flow cell, in single pass, was employed for flow CCE. The effect of applied current, flow rate, and interelectrode gap were considered for optimal results.